Effects of thermal histories on carbon fiber/polyamide 6 microcomposite load transfer efficiency: Crystallization, modulus, and measurement. Issue 1 (11th January 2016) - Li, Hongfu; Zhang, Yanfei; Wang, Yang; Zhang, Boming
Abstract : In this work, load transfer efficiency (LTE) is quantitatively expressed as a specific formula and characterized through electrical resistance method. Single carbon fiber (CF) reinforced polyamide 6 (PA6) microcomposites with eight different thermal histories were prepared. Polarizing optical microscope (POM) was used to observe crystal morphologies. Tensile properties of neat PA6 with different thermal histories were tested. All the above results show that electrical resistance method is an effective way to characterize CF/PA6 microcomposite interface LTE. Water quenched CF/PA6 microcomposites have a highest LTE of 94.2%, while LTE decreased to 34.3% at the bottom for 200°C annealing treated specimens. POM results show that decreasing nonisothermal cooling rate results in larger spherulites and transcrystallites but lower nucleus density, while annealing treated samples nearly have no change and still keep quite transparent. It is also very interesting to find that there is an antisymmetric relationship between LTE and matrix modulus of nonisothermal/isothermal crystallization samples, and LTE drops more for the annealing treated specimens under the similar modulus, which ascribes to radial residual stress releasing during annealing treatment. POLYM. COMPOS., 39:102–109, 2018. © 2016 Society of Plastics Engineers